Odpowiedź :
1.Ca(OH)2+H2SO4=CaSo4+2H2O
2. CaO + SO3 -> CaSO4
3.Ca(OH)2 + SO3 -> CaSO4 + H2O
4.Ca + H2SO4 -> CaSO4 + H2
2. CaO + SO3 -> CaSO4
3.Ca(OH)2 + SO3 -> CaSO4 + H2O
4.Ca + H2SO4 -> CaSO4 + H2
metal + kwas → sól + wodór
Ca + H2SO4 → CaSO4 + H2
wodorotlenek zasadowy + kwas → sól + woda
Ca(OH)2 + H2SO4 → CaSO4 + 2 H2O
tlenek zasadowy + tlenek kwasowy → sól + woda
CaO + SO3 → CaSO4
tlenek zasadowy + kwas → sól + woda
CaO + H2SO4 → CaSO4 + H2O
Pozdro)
Ca + H2SO4 → CaSO4 + H2
wodorotlenek zasadowy + kwas → sól + woda
Ca(OH)2 + H2SO4 → CaSO4 + 2 H2O
tlenek zasadowy + tlenek kwasowy → sól + woda
CaO + SO3 → CaSO4
tlenek zasadowy + kwas → sól + woda
CaO + H2SO4 → CaSO4 + H2O
Pozdro)